Does Green Finance and ESG Enhance Firm Performance? Empirical Evidence from Indonesia in Emerging Markets - Naila Afifah Sharfina; Busra Busra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the impact of Environmental, Social, and Governance (ESG) practices and green financing on firm performance dynamics and volatility in the Indonesian capital market. Using a quantitative time-series approach with secondary data, the sample consists of six major companies listed on the Indonesia Stock Exchange—BBRI, BBNI, UNVR, PGEO, TLKM, and ADRO—over the period 2019–2024. The analysis employs an ARIMA–GARCH model to capture the dynamic relationship between ESG, green financing, and weekly stock returns. The findings indicate that ESG scores and green financing significantly affect changes in ESG performance, with a negative short-term relationship. Moreover, volatility persistence is observed, suggesting that ESG stability is highly sensitive to past shocks and market dynamics. These results imply that the benefits of ESG implementation and green financing are primarily long-term in nature and are not fully reflected in short-term market stability in emerging markets such as Indonesia. This study provides important insights for firms, investors, and regulators in strengthening sustainable finance strategies.